WOMEN LABOUR DOUBLE ROLE ON FAMILY INCOME (CASE STUDY OF FISH AUCTION PLACE IN GAUNG PADANG VILLAGE) - Eliza, Yulina; Putra, Trimardi Jaya (jurnal ekonomi, 2018)
Based on the economic needs of the average family in Kelurahan Gaung Kota Padang has not been fulfilled because the income of family head is relatively low, so to fulfill the needs of the housewife family in the village Gaung tried to suffice Needs by working as a female laborer. The purpose of the research is to know how much contribution is given by women working as workers. The research took place in February 2018. Data retrieval in the form of primary data and secondary data. The primary data is obtained through a direct interview to 30 respondents using kuisoner and secondary data obtained from Padang City Fisheries and Marine Service. Sampling technique is Purposive Sampling is a technique by considering the criteria of respondents are women who work as workers, still have a husband and status marry and have dependents in the family. The resulting Data is presented in a table Form and analyzed descriptively and reflects the magnitude of the contribution given by the female laborer. The amount of contributions given by female laborers is derived from a percentage between the wife's income, husband's income and also the child (who has worked). The results showed that the percentage of women working as workers contributed 44.62%, meaning that the contribution of women's income to family income in Gaung village is good. Good meaning is that the income gained by women by working as laborers has been very helpful to the husband in fulfilling and suffice in the household every day. This means that without the contribution of women, the needs in the family cannot be fulfilled. Berdasarkan kebutuhan ekonomi keluarga rata-rata di Kelurahan Gaung Kota Padang belum tercukupi karena pendapatan kepala keluarga relatif rendah, sehingga untuk memenuhi kebutuhan keluarga ibu rumah tangga yang ada di Kelurahan Gaung berusaha mencukupi kebutuhan dengan bekerja sebagai buruh perempuan. Tujuan penelitian adalah untuk mengetahui berapa besar kontribusi yang diberikan oleh perempuan yang bekerja sebagai buruh. Penelitian dilaksanakan pada bulan Februari 2018. Pengambilan data berupa data primer dan data sekunder. Data primer diperoleh melalui wawancara langsung kepada 30 responden dengan menggunakan kuisoner dan data sekunder diperoleh dari Dinas Perikanan dan Kelautan Kota Padang. Teknik pengambilan sampel adalah Purposive Sampling yaitu teknik dengan mempertimbangkan kriteria responden adalah perempuan yang bekerja sebagai buruh, masih memiliki suami dan berstatus menikah dan memiliki tanggungan dalam keluarga. Data yang dihasilkan disajikan dalam bentuk tabel dan dianalisis secara deskriptif dan menggambarkan besarnya kontribusi yang diberikan oleh buruh perempuan. Besarnya kontribusi yang diberikan oleh buruh perempuan diperoleh dari persentase antara pendapatan istri, pendapatan suami dan juga anak (yang sudah bekerja). Hasil penelitian menunjukan bahwa persentase perempuan yang bekerja sebagai buruh memberikan kontribusi sebesar 44,62 %, artinya bahwa kontribusi pendapatan perempuan terhadap pendapatan keluarga di Kelurahan Gaung baik. Baik artinya adalah dengan pendapatan yang diperoleh perempuan dengan bekerja sebagai buruh sudah sangat membantu suami dalam memenuhi dan mencukupkan kebetuhan dalam rumah tangga setiap hari. Artinya bila tanpa kontribusi dari perempuan maka kebutuhan dalam keluarga belum dapat tercukupi.